Fast, Efficient, and Versatile Synthesis of 6-amino-5-carboxamidouracils as Precursors for 8-Substituted Xanthines - Marx, Daniel; Wingen, Lukas M.; Schnakenburg, Gregor; Müller, Christa E.; Scholz, Matthias S. (Frontiers in Chemistry, 2019)
Substituted xanthine derivatives are important bioactive molecules. Herein we report on a new, practical synthesis of 6-amino-5-carboxamidouracils, the main building blocks for the preparation of 8-substituted xanthines, by condensation of 5,6-diaminouracil derivatives and various carboxylic acids using the recently developed non-hazardous coupling reagent COMU (1-[(1-(cyano-2-ethoxy-2-oxoethylideneaminooxy)dimethylaminomorpholinomethylene)]methanaminium hexafluorophos-phate). Optimized reaction conditions led to the precipitation of pure products after only 5 to 10 min of reaction time. The method tolerates a variety of substituted 5,6 diaminouracil and carboxylic acid derivatives as starting compounds resulting in most cases in more than 80% isolated yield. Regioselectivity of the reaction yielding only the 5-carboxamido-, but not the 6-carboxamidouracil derivatives, was unambiguously confirmed by single X ray crystallography and multidimensional NMR experiments. The described method represents a convenient, fast access to direct precursors of 8-substituted xanthines under mild conditions without the necessity of hazardous coupling or chlorinating reagents.